APLIKASI PENDEKATAN LAND RENT DALAM MENGANALISIS ALIH FUNGSI LAHAN SAWAH MENJADI KEBUN KELAPA SAWIT - Fahri, Anis (Informatika Pertanian, 2016)
Land rent of paddy field is lower than oil palm and it encourages farmers to convert wetland to oil palm plantations.This study aimed to determine the impact of land use on the welfare of rice farmers. The experiment was conducted in Kampar district from April to December 2013. Data were collected through a field survey of 30 rice farmers and 30 farmers who converted wetland to oil palm plantations. Land rent value of paddy rice farming management was then compared with the land rent of oil palm plantations. The alignment of the calculation of land rent value of both commodities was carried out by PVNR value approach to timing analysis for 25 years (according to the economic lives of oil palm plantations) and a discount rate of 10%. The economic analysis showed that the average rice farming land rent value was Rp.9.834.727/hectare/year. The average land rent value of oil palm was Rp 16.255.090/hectare/year. PVNR - land rent value of the rice farming was Rp. 89.200.977 / hectare, while the value of farm land rent - PVNR of oil palm was Rp. 111.388.769/hectare . PVNR - land rent of oil palm was higher by 25 % than that of paddy. The result indicated that the ratio of land rent oil palm was 1.25 times higher than wetland. The welfare of rice farmers was lower with the value of NTPRP 0,57 than oil palm farmers with the value of NTPRP 0,70.